2018
DOI: 10.1111/ajco.13102
|View full text |Cite
|
Sign up to set email alerts
|

Association between PD‐L1 expression and lymph node metastasis in cutaneous squamous cell carcinoma

Abstract: Aim To clarify the relationship between programmed cell death ligand 1 (PD‐L1) expression in cutaneous squamous cell carcinoma (cSCC) and clinicopathological variables. Methods We examined PD‐L1 expression in tumor cells (TCs) and tumor infiltrating immune cells (ICs) in 46 cases of cSCC by immunohistochemistry. In each case, we employed two methods—intensity and proportion scores—to evaluate PD‐L1 expression in TCs. For the evaluation of PD‐L1 expression in ICs, only the proportion score was used. Association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…In reported studies, 20%–70% of the patients with SCC had PD-L1 expression in tumor cells. [ 7 8 9 10 11 12 13 ] In the present study, 52.5% of the patients had PD-L1 expression in tumor cells. Although the expression of PD-L1 in sun-exposed skin and that in nonsun-exposed skin were evaluated in some previous studies, no statistically significant difference was found.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…In reported studies, 20%–70% of the patients with SCC had PD-L1 expression in tumor cells. [ 7 8 9 10 11 12 13 ] In the present study, 52.5% of the patients had PD-L1 expression in tumor cells. Although the expression of PD-L1 in sun-exposed skin and that in nonsun-exposed skin were evaluated in some previous studies, no statistically significant difference was found.…”
Section: Discussionsupporting
confidence: 47%
“…Although the expression of PD-L1 in sun-exposed skin and that in nonsun-exposed skin were evaluated in some previous studies, no statistically significant difference was found. [ 12 13 ] However, the number of patients with SCC in nonsun-exposed skin in those studies was relatively small. [ 12 13 ] In our study, a significant correlation was found between sun exposure and expression of PD-L1 in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether this reflects effects of altered microenvironment and/or evasion of immune surveillance is unclear. Kamiya et al73 found that a higher intensity of PD-L1 staining, but not the proportion of tumor cells with PD-L1 staining, correlated with nodal metastasis in cutaneous SCC. In contrast, Garcia-Pedrero et al74 found that PD-L1 expression in more than 25% of tumor cells correlated with lymph node metastasis in head and neck cutaneous SCC.…”
Section: Discussionmentioning
confidence: 99%
“…metastatic cSCC, it has not been reported whether response is related to PD-L1 expression status [5,[42][43][44].…”
Section: Pd-l1 Expressionmentioning
confidence: 99%